Pemberdayaan Keluarga Prasejahtera Melalui Program Keluarga Harapan - Ade Sulistiawati; Syamsuddin RS; Encep Taufik Rahman (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
The problems that are still not well mapped are related to poverty. Poverty experienced by the community affects the welfare of family life. The purpose of this study was to find out and analyze the program launched by the Family Hope Program, the process of implementing the Family Hope Program, and the results of empowering underprivileged families through the Family Hope Program in Bongas Kulon Village. This research is a qualitative research using descriptive method. The results of his research are the empowerment program for underprivileged families through disbursement of social assistance funds and Family Capacity Building Meetings (P2K2). The implementation of the Family Hope Program goes through several stages, namely the preparation, implementation, evaluation and termination stages. In addition, the results of empowering underprivileged families can be viewed from health aspects in early childhood, educational aspects, and social welfare aspects for the elderly in accessing education and health facilities.